Trauma Event of Preparatory School Students in the Families of Political Martyrs in Wasit Governorate - Nasir Khalifa, Rashid; Sabeeh Abid, Siaq (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims at exploring: - The level of acceptance of trauma event among high preparatory school students of the families of political martyrs in Wasit governorate according to gender (males/ females). To achieve the aim of the research, the two researchers have constructed a scale for measuring trauma event and used the nterview as a tool to verify the validity and reliability of the items of the scale. The interview is carried out when the researchers have visited the Political Martyrs Foundation in Wasit Governorate and met the sample members. In addition, the sample members have been asked to take photographs for them to be attached to the research appendices. In order to treat the data statistically to achieve the goal of the research, the researchers have used the following statistical means:- 1- Pearson correlation coefficient. 2- Test-retest The descriptive statistical indicators of the scale have been ascertained and the researchers have concluded the following:- The individuals of the current research sample do not possess a level of acceptance of the event’s trauma.